Degradacja zasady jawności: rewolucja czy kontynuacja przyjętej strategii? - Iaroslavska, Marianna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
Ustawodawca coraz częściej dąży do przyspieszania postępowania kosztem zasady jawności. Artykuł przedstawia analizę zmian, jakie zaszły w odniesieniu do zasady jawności w postępowaniu cywilnym, a także dylematów, jakie pojawiły się z powodu ograniczania jawności. Rozważania koncentrują się wokół tematyki naczelnych zasad procesu, w szczególności zasady jawności, instytucji ograniczających zasadę jawności oraz konfliktu między zasadą jawności a postulatem szybkości.

The legislature increasingly seeks to speed up proceedings at the expense of the principle of openness. The article presents an analysis of the changes that have taken place with regard to the principle of openness of court hearings in civil proceedings, as well as the dilemmas that have arisen due to the restriction of openness. The discussion focuses on the subject of the guiding principles of the trial, in particular the principle of openness, institutions that limit the principle of openness, and the conflict between the principle of openness and the demand for speed proceedings.
Degradation of the principle of openness of court hearings: revolution or continuation of the adopted strategy?
Keywords: jawność; zasady naczelne; zasady procesowe; postulat szybkości; szybkie postępowanie; brak jawności; COVID-19; the principle of openness of court hearings; principal principles; procedural principles; demand for speed of proceedings; speedy proceedings; lack of openness